Surveillance of Chagas disease vectors in Ceará State, Northeastern Brazil - de Alencar, Maria Janiele; Ramos da Silva, Abel Brasil; Bezerra, Cláudia Mendonça; Alencar, Carlos Henrique; Martins, Victor Emanuel Pessoa (Journal of Health & Biological Sciences, 2021)
Objective: Describe the spatial distribution, temporal trend and the natural infection rates by Trypanosoma cruzi in triatomines captured in Ceará State, between 2003 and 2014. Methods: Chagas Disease Control Program data were used to describe triatomine species circulating, their distribution in the state, the capture places (intradomicile and peridomicile), and the rates of natural infection by T. cruzi, between 2003 and 2014. Results: During this period, 401,721 triatomines were captured in 89.1% of the municipalities of the State, belonging to the species Triatoma pseudomaculata (53.9%), Triatoma brasiliensis (40.5%), Rhodnius nasutus (1.9%), Panstrongylus megistus (1.5%), Panstrogylus lutzi (1.3%), Triatoma rubrofasciata (0.8%), Panstrongylus geniculatus (< 0.1%), and Triatoma petrochiae (< 0.1%). Most of the specimens were caught in peridomicile areas (83.0%), with emphasis on T. pseudomaculata and T. brasiliensis, while P. lutzi was predominant in the intradomicile. P. lutzi had the highest infection rate by T. cruzi (7.8%), while T. pseudomaculata (0.9%), T. brasiliensis (1.0%), and P. megistus (1.3%) had the lowest rates. Conclusions: The occurrence of an enzootic cycle of T. cruzi and the presence of synanthropic animals that provide a source of blood meals to triatomines increases the risk of its transmission to humans, requiring constant vigilance by the sanitary authorities.